Bioconversion of Edamame Soybean Waste Using Black Soldier Fly Larvae on Substrate Consumption and Waste Reduction Index: Biokonversi Limbah Kedelai Edamame Menggunakan Larva Black Soldier Fly Terhadap Konsumsi Substrat dan Indeks Reduksi Limbah - Safitri, Sofiyah; Eurika, Novy; Priantari, Ika (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2025)
This study aimed to measure substrate consumption and waste reduction index of edamame soybean using Black Soldier Fly (BSF) larvae as a bioconversion agent. This study used a Completely Randomized Design (CRD) with three treatments: unfermented edamame soybean waste (F0), fermented for 7 days (F7), and fermented for 14 days (F14). The observed bioconversions included substrate consumption and waste reduction index (WRI). Data analysis used analysis of variance with a confidence level of 5%. The results showed that waste fermentation significantly affected substrate consumption and waste reduction index. The highest average substrate consumption was obtained in treatment F14 (57.96±7.37), followed by F7 (41.61±6.73) and F0 (28.51±4.97). Likewise, with the waste reduction index, the F14 treatment showed the highest reduction (2.37±0.61), followed by F7 (3.46±0.56) and F0 (4.83±0.41). This shows that the longer the fermentation, the higher the substrate consumption and the effectiveness of waste reduction by BSF larvae.